A relação família e escola na pedagogia da alternância: um estudo nas casas familiares rurais de Candói e Rio Bonito do Iguaçu - Santos, Cilmara Cristina dos (2013)
Thinking about the role of the family in the educational context of his sons to become the face of new thematic fundamental changes in society in the XXI century. The theme about family and school involves a set of actors and has been discussed constantly in recent decades as a cornerstone to the educational process of children and youth. This dissertation is a research topic about family and school in the Pedagogy of Alternation in Rural Family Houses Candói of Iguaçu and Rio Bonito, both located in Macau Cantuquiriguaçu in Paraná State. We conducted a social survey, a qualitative, with the data collection instrument observations, interviews and visits to properties. We analyzed comparatively the two CFRs how is the relation of families with them and with the teaching-learning process of their children. It was understood that family participation in the Pedagogy of Alternation besides constituting itself as a pillar of this methodology is also intrinsic to sharing knowledge between parents and children within the social context to which they belong. It was noticed that families need greater incentives and requirements to exercise their right to participate in the CFRs, because the properties are located in rural areas, often difficult to access and long distance Schools.